MORPHOLOGY AND COMPOSITION FORMATION IN NICKEL SILICON NITRIDE (NI/SI3N4) COMPOSITE LAYERS USING PULSE ELECTRODEPOSITION METHOD: PEMBENTUKAN MORFOLOGI DAN KOMPOSISI PADA LAPISAN KOMPOSIT NICKEL SILICON NITRIDE ( NI/SI3N4 ) MENGGUNAKAN METODE ELEKTRODEPOSISI ARUS PULSA - Irsya Luthfiah Ramadhyagita; Esmar Budi; Teguh Budi Prayitno (Joint Prosiding IPS dan Seminar Nasional Fisika, 2025)
Metal plating is commonly used in industry to modify surface morphology without altering its original properties. A composite Ni/Si3N4 layer on Tungsten Carbide (WC) was formed using a current density of 0.25 mA/mm2 to analyze the surface morphology and composition of the Ni/Si3N4 composite layer. The formation process employed the pulsed current electrodeposition method at a temperature of 40°C, with a stirring rate of 600 rpm for 1 hour. The solution composition included 0.38 M Ni2SO4·6H2O, 0.17 M Ni2Cl2·6H2O, 0.6 g/L Si3N4, 0.6 g/L SDS (Sodium Dodecyl Sulfate), and 0.49 M H3BO3. The results showed the presence of Ni and Si metal elements with mass compositions of 85.17% and 0.82%, respectively. Surface morphology scanning revealed a smooth surface with slight agglomeration on the substrate.